Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kinerja Dimediasi Motivasi Kerja - Uswatun Hasanah; Tessalonika Anggraini Tinambunan; Akirom Wildan (Jurnal Ilmu Manajemen, 2026)
This study aims to determine the influence of physical work environment and work load on employee performance mediated by work motivation at manufacture. This research was carried out quantitatively with data collection techniques in the form of observation, literature studies and questionnaires. The population was 261 with 119 samples, the sample drawing technique was Proportionate stratified random sampling. The results of this study show that the physical work environment has a negative and insignificant effect on employee performance. Work load has a positive effect on employee performance. The physical work environment on employee performance mediated by work motivation has a significant positive influence. Work load on employee performance mediated by work motivation has a significant positive  influence.